Risk Management for 4-H Youth Development Work: Fundraising and Fundhandling: 4H-FSV-375/4H386, 2/2018 - Pracht, Dale; Pennisi, Alexandria; Davis, Paula; Prevatt, Stefanie; Psikogios, Janet (EDIS, 2018)
This 6-page document is one in the series Risk Management for 4-H Youth Development Work. It reviews policies and best practices for handling 4-H program funds and conducting 4-H fundraisers. Written by Dale Pracht, Alexandria Pennisi, Paula Davis, Stefanie Prevatt, and Janet Psikogios and published by the UF/IFAS 4-H Youth Development Department, January 2018. http://edis.ifas.ufl.edu/4h386